Critical coupling in plasmonic chain for efficient energy trapping - Marius Crouzier; Fei Mao; Giovanni Magno; Vy Yam; Carlos Alonso-Ramos; Jean-René Coudevylle; Etienne Herth; Christophe Dupuis; Xavier Leroux; Thomas Lopez; Béatrice Dagens (Scientific Reports)
Abstract Plasmonic nanoparticles can concentrate energy at the nanometer scale, offering promising applications across multiple fields such as lab-on-chip technologies and photonic circuits. A crucial requirement for these applications is achieving efficient coupling between the nanoparticles and the excitation signal. Plasmonic nanoparticle chains can guide light at subwavelength scale and can be excited through coupling to a dielectric waveguide. In this manuscript, we propose a novel configuration for the plasmonic chain-dielectric waveguide structure that allows the chain to be freely positioned relative to the waveguide. We demonstrate the existence of a critical coupling regime between a silicon waveguide and a plasmonic chain, achieved through precise control of their separation. In this regime, the plasmonic chain transitions from its well-known transmission mode to a new cavity state, trapping 99% of the waveguide’s energy. This result paves the way for efficiently addressing nanostructures through integrated waveguides, enabling efficient optical nano-tweezers, sensors or nano-heaters.